DI BAWAH LANGIT TAK BERBINTANG KARYA UTUY TATANG SONTANI: TINJAUAN SASTRA PERJALANAN CARL THOMPSON - Windayanto, Riqko Nur Ardi (ATAVISME, 2022)
Di Bawah Langit Tak Berbintang (DBLTB) by Utuy Tatang Sontani is a travel literature because it narrates travel, fulfills the formal-aesthetic characteristics of travel literature, and reconstructs travel experiences in a novelistic way. This study explains aspects of travel literature and the author's ideology with Thompson's theory of travel literature. The first problem data are verbal units in DBLTB which tell about self-other, movement, room, meeting, agenda, and writing, which are collected using the note-taking technique. Data ideology is narratives from social, cultural, and ideological texts, which are collected by literature study. The data are analyzed by content analysis and Laclau and Mouffe’s discourse analysis. This study shows that Utuy involved himself as I, a traveler in Indonesia and China. The journey makes him arrives at spaces, such as Bandung, Jakarta, Peking, Canton, Cengkareng, sanatoriums, and Cing Tao, and brings him meets with others, both people, places, and activities. In its journey, the dominant world is described subjectively, which then shows the author's agenda, namely and defends his ideology, namely individualism.